FUNGSI PEMERINTAH DALAM PENANGANAN PENGEMIS DAN PENGAMEN ANAK DI KECAMATAN BANYUWANGI - Pratiwi, Nanda Eka Pratiwi; Rahayu, Sri Rahayu; Priyanto, Hary Priyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2024)
Government Function in Handling Themes and Securities. This study aims to analyze the function of government in handling beggars and buskers in Banyuwangi District. The method used is related to the handling of beggars and buskers, namely: descriptive qualitative based on the principle of William N. Dunn. The results of this study prove that the government has not succeeded in making efforts to deal with beggars and buskers because the poor continue to beg and busking. In the efforts carried out as regulated in Law Number 35 Year 2014, Regarding: Child Protection and Regional Regulations of Banyuwangi, Number 11 Year 2014 Regarding: Public Order and Peace of Society. the government should be able to make policies and implement them well so that they can deal with problems in handling beggars and buskers in Banyuwangi District. The goal is to be right on target in handling and providing solutions to beggars and buskers.